Gendered Language and Workspace Segregation in SMEs: A Case Study of Unpacking Stereotypes in Pempek 26 Ilir Palembang - Neisya, Neisya; Trisninawati, Trisninawati; Aprilia, Fitria (Journal of Languages and Language Teaching, 2025)
This research investigates how language use and gender segregation in the SMes of Pempek 26 Ilir Palembang contribute to the representation of gender identity. This phenomenon is significant, as workplaces in Indonesia, especially in Palembang, persistently display notable gender segregation. In the quest for gender parity, employees’ identities are continuously replicated, with language being a crucial role. This qualitative research utilizes documentation, observation, and interviews for data collection. Meanwhile, the Miles and Huberman approach, that entails data reduction, presentation, and conclusion drawing, is used for data analysis. Butler’s theory of gender performativity serves as the analytical lens, adopting a case study approach. The results show that most of employees and managers of SMEs in the Pempek 26 Ilir area aware the existing gender segregation. Stereotypes are the cause of this segregation. This division results from assumptions that say women belong in jobs requiring endurance and attention to detail, while males belong in jobs that are more physically demanding. The language used by employees is courteous but informal, and the subjects of conversation differ greatly. Male and female employees typically focus on work or interests, while female employees are more talkative about personal and family problems. Overall, these findings show that heteronormative gender performativity is reinforced in the work environment of Indonesian SMEs, especially in Pempek 26 Ilir Palembang, where males are seen as stronger and more reserved and women as weaker but more communicative.